X-ray micro-CT scanning of tests of three planktic foraminiferal species to clarify dissolution process and progress - Shinya Iwasaki; Katsunori Kimoto; Yusuke Okazaki; Minoru Ikehara (PANGAEA, 2019)
Evaluation of foraminiferal test dissolution in deep-sea sediments facilitates reconstruction of seawater chemistry. Here we observed test dissolution processes of the planktic foraminifera Trilobatus sacculifer, Globigerinoides ruber, and Neogloboquadrina dutertrei from mid-latitudes of the western North Pacific; in these three species, we tested the ability of a new dissolution index using data from X-ray micro-computed tomography scanning (XMCT). Although the dissolution process of foraminiferal tests differed slightly among species, dissolution of all species was equally assessed by the calcite density distribution (%Low-CT-number calcite volume) calculated from the CT number histogram. As for T. sacculifer and G. ruber, the test area density, a conventional proxy for assessing test condition based on weight measurement, is affected by variance in the thickness of the outermost chamber wall; thus, this conventional proxy can be affected by sea surface conditions during test calcification. In contrast, the relationship between the %Low-CT-number calcite volume of tests and the deep seawater calcite saturation state suggests that XMCT scanning is applicable for evaluating the intensity of foraminiferal test dissolution at the under-saturated deep seafloor in this area and is an invaluable proxy for detecting deep seawater carbonate ion concentration changes on glacial-interglacial timescales.
Supplement to: Iwasaki, Shinya; Kimoto, K; Okazaki, Y; Ikehara, M (2019): Micro-CT Scanning of Tests of Three Planktic Foraminiferal Species to Clarify DissolutionProcess and Progress. Geochemistry, Geophysics, Geosystems, 20(12), 6051-6065, https://doi.org/10.1029/2019GC008456